Resepsi Khalayak mengenai Pemberitaan Rizieq Shihab terkait Chat Konten Pornografi di Instagram - Ardhia Nugraha; Hedi Pudjo Santoso (Interaksi Online, 2018)
This study discusses about report to Rizieq Shihab. One of the media that preaches about Rizie Shihab related to pornographic content chat is an Instagram account that has many followers, named @agus_bunyu. Instagram hegemonized readers accordingly with what media offers. This study is intended to describe public’s interpretation to criminalization discourse in preaching on Instagram. This type of study is qualitative and uses reception analysis approaching. The public is regarded as the producer of meaning, not only as consumer of media contents. Public will receives news that contains supposition of pornographic content chat of Rizieq Shihab in Instagram that related to their social, culture and knowledge background. This research uses Stuart Hall’s encoding-decoding model to know the public’s interpretation. The meaning producing process includes the content of the text to observe dominant means through preferred reading using semiotic analysis to see category of public’s menaing in dominant respond, negotiation or opposition. The result of this research shows that public is active in interpreting the preaching of Rizieq Shihab’s on suspicion of pornographic content chat in Instagram that they receive. Public’s interpretation is divided into three meaning positions: dominant reading, negotiated reading, and oppositional reading. The public that included into dominant reading interprets the preaching of Rizieq Shihab on suspicion of pornographic content chat suited with dominant meaning that offered by media. Meanwhile, the public in negotiated reading position interprets the preaching of Rizieg Shihab on suspicion of pornographic content chat with their own interpretation. This group of audience is not only regarding this preaching of Rizieq Shihab on suspicion of pornographic content chat from Rizieq Shihab side, which is being criminalized, but also consider the process that is being done by the Police in handling this case is properly handled. On the other hand, the audience that included into oppositional reading interprets this preaching of Rizieq Shihab on suspicion of pornographic content chat is entirely different and contrast with dominant meanings from the preaching.